High Frequency of Recurrent Falls Among Prefrail and Frail Women With and Without HIV. (1st June 2021) - Sharma, Anjali; Hoover, Donald R.; Shi, Qiuhu; Gustafson, Deborah R.; Plankey, Michael; Tien, Phyllis C; Weber, Kathleen M.; Vance, David E.; Floris-Moore, Michelle; Bolivar, Hector H.; Golub, Elizabeth T.; Holstad, Marcia M.; et al.
Abstract : Background: Frailty may occur at younger ages among HIV+ populations. We evaluated associations of the frailty status with self-reported single and recurrent falls in the Women's Interagency HIV Study (WIHS). Methods: The frailty status was defined using the Fried Frailty Phenotype (FFP) among 897 HIV+ and 392 HIV− women; median age 53 years. Women were classified as robust (FFP 0), prefrail (FFP 1–2), and frail (FFP 3–5). Stepwise logistic regression models adjusting for the HIV status and study site were fit to evaluate associations of the FFP with self-reported single (1 vs. 0) and recurrent falls (≥2 vs. 0) over the prior 12 months. Results: HIV+ women were less likely to be frail (9% vs. 14% vs. P = 0.009), but frequency of falls did not differ by the HIV status. In multivariate analyses, recurrent falls were more common among prefrail [adjusted odds ratio (AOR) 2.23, 95% confidence interval (CI): 1.40 to 3.57, P = 0.0008] and frail (AOR 3.61, 95% CI: 1.90 to 6.89, P < 0.0001) than robust women. Among HIV+ women, single (AOR 2.88, 95% CI: 1.16 to 7.20, P = 0.023) and recurrent falls (AOR 3.50, 95% CI: 1.24 to 9.88, P = 0.018) were more common among those who were frail; recurrent, but not single falls, were more common among prefrail than robust HIV+ women (AOR 2.00, 95% CI: 1.03 to 3.91, P = 0.042). Conclusions: HIV+ women were less likely to be frail. Compared with robust women, prefrail and frail women with and without HIV were more likely to experience single or recurrent falls within a 12-month period. Additional studies are needed to develop interventions that decrease development of frailty and reduce risk of recurrent falls among HIV+ women.